2018
DOI: 10.1021/acssuschemeng.8b03495
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Waste Batteries: Recovery of Valuable Resources or Reutilization as Functional Materials

Abstract: Massive spent batteries cause resource waste and environmental pollution. In the last decades, various approaches have been developed for the environmentally friendly recycling of waste batteries, as attractive secondary resources. In the present work, the recent progress in the recycling strategies is reviewed, with emphasis on the recovered products (metals and compounds) with high purity and the reutilization of the waste batteries as functional materials (electrode materials in energy storage devices, cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 105 publications
0
24
0
1
Order By: Relevance
“…Sample CP3, displayed a significantly higher C dl value (2.57 mF/cm 2 ) over CP1 (0.56 mF/cm 2 ) and CP2 (0.77 mF/cm 2 ), and CP4 (0.57 mF/cm 2 ). The larger C dl indicated that CP3 had a significantly increased number of exposed active sites and a higher efficient mass and charge transport capability [51]. Furthermore, as demonstrated in Figure 6e, CP3 had a larger current density at the same scan rate compared to the rest of the samples.…”
Section: Electrocatalytic Performancementioning
confidence: 94%
See 1 more Smart Citation
“…Sample CP3, displayed a significantly higher C dl value (2.57 mF/cm 2 ) over CP1 (0.56 mF/cm 2 ) and CP2 (0.77 mF/cm 2 ), and CP4 (0.57 mF/cm 2 ). The larger C dl indicated that CP3 had a significantly increased number of exposed active sites and a higher efficient mass and charge transport capability [51]. Furthermore, as demonstrated in Figure 6e, CP3 had a larger current density at the same scan rate compared to the rest of the samples.…”
Section: Electrocatalytic Performancementioning
confidence: 94%
“…When a metal oxide electrode is inserted into an electrolyte, an electrical double layer or space charge layer is formed. For p-type semiconductors, the space charge layer is negligible [51]. So, as a catalyst material, a p-type semiconductor is more suitable.…”
Section: Electrocatalytic Performancementioning
confidence: 99%
“…The “waste to wealth” concept is widely accepted in the recycling of spent LIBs 75,76 . Other than the reutilization in the LIB manufacture, massive interests have been aroused in developing new applications in an economic manner, exploring suitable applications not only for the cathode materials but also for the relatively low value‐contained graphite anode.…”
Section: Development Of Multifarious Applicationsmentioning
confidence: 99%
“…[1][2][3][4] The rising demand for EV and the low accessibility to raw materials are threatening the LIBs production and urge the instant necessity of recycling to employ the valuable materials. [1,2,[16][17][18]20,22,[33][34][35][36][37][38][39][40][41][42] In this review, we discuss first time in detail about the reutilization of spent LIBs materials/recovered materials in various fields including LIB, supercapacitors, oxygen evolution reaction (OER), adsorption, photocatalytic studies, etc. [27,28] In chemical process, researchers mostly prefer hydrometallurgical route for the recycling of spent LIBs attributable to the great advantages such as low energy conditions, minimization of waste water, and higher percentage recovery of metals with high purity.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have combined the processes to recover the metals from spent LIBs . Thus far, metal recovery process, technologies being used by various companies, and regulations and legislations regarding spent LIBs have been already reviewed more . In this review, we discuss first time in detail about the reutilization of spent LIBs materials/recovered materials in various fields including LIB, supercapacitors, oxygen evolution reaction (OER), adsorption, photocatalytic studies, etc.…”
Section: Introductionmentioning
confidence: 99%